Incidence and risk factors for cognitive impairment in rural elderly populations in Costa Rica - Nadel, Jeffrey L. (2014)
Risk factors for the onset of cognitive impairment in Costa Rica are not well understood, despite a substantial elderly population stemming from a higher than average life expectancy for the western hemisphere. To investigate the risk factors that predict the onset of cognitive impairment in the rural elderly of Costa Rica, a modified version of the Mini Mental State Exam—designed for illiterate populations—was administered to 90 elderly inhabitants of San Carlos, Alajuela, Costa Rica between April and May of 2011. Subsequently, each participant took a structured interview assessing viability of risk factors and behaviors potentially contributing to a diagnosis of cognitive impairment. Results showed strong dependencies between age (p=0.0001), education level (p=0.0095), the ability to read (p=0.0001) and write (p=0.0153), frequency of reading (p=0.0011), use of puzzles and mind games (p<0.0001), vocation (p=0.0225), area of residence (p<0.0001), comorbid mental diseases (p=0.0005), history of stroke or brain trauma (p=0.0104), urinary or renal problems (p=0.0443), consistent cooking practices (p=0.0262) and number of living companions (p=0.0299) in susceptibility for developing cognitive impairment. The study concluded that high intellectual use, or lack thereof, during the lifetime of a person was a predictor for cognitive status later in life. In addition, comorbid mental disorders, including neurological trauma due to stroke, impeded normal cognitive function. Future research should examine incidence and risk factors of cognitive impairment in urban, more educated populations.  Jeffrey L. Nadel Diana UlateAssociated Colleges of the Midwest, San Pedro Montes de Oca, Costa Rica; jeffrey.nadel@gmail.com, acmcostarica@acm.edu